Nanomagnetic beads and preparation method and application thereof

By wrapping silica and chitosan on the surface of Fe3O4 nanomagnetic particles and coupling affinity proteins, nanomagnetic beads with large specific surface area and high adsorption capacity are prepared, which solves the shortcomings of existing magnetic nanocomposites in antibody purification and achieves efficient antibody separation, purification and enrichment.

CN119771343APending Publication Date: 2025-04-08BEAVERNANO TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979156.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

Smart Images

  • Figure BDA0005221120550000111
    Figure BDA0005221120550000111
  • Figure BDA0005221120550000112
    Figure BDA0005221120550000112
  • Figure BDA0005221120550000113
    Figure BDA0005221120550000113
Patent Text Reader

Abstract

The present invention relates to the field of biomedical detection, and in particular to nanomagnetic beads and their preparation methods and applications. The present invention accurately and reasonably designs a nanomagnetic bead with a core-shell structure, and at the same time provides a preparation method of the nanomagnetic bead, which has controllability and flexibility, and is suitable for large-scale stable production and promotion and application. The magnetic material forming the core-shell structure of the nanomagnetic bead has a large specific surface area and high adsorption capacity. In the field of monoclonal antibody production, these magnetic materials can be used to pre-treat complex samples to achieve the purpose of effective separation, purification and enrichment. It has been verified by experiments that the IgG loading of the magnetic nanoparticles prepared by the present invention can reach up to 173 mg / mL.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical detection, and in particular to nanomagnetic beads and a preparation method and application thereof. Background Art

[0002] Antibody purification refers to the process of extracting antibodies from samples such as serum, ascites or cell culture supernatant. Purified antibodies are suitable for a variety of applications. Magnetic bead-based antibody purification is a dispersed solid phase extraction technology that uses magnetic or magnetizable materials as adsorbents dispersed in the sample being processed, rather than the usual method of passing the sample through a column filled with solid phase affinity materials. During the purification process, the magnetic adsorbent is directly added to the sample solution or sample suspension. After shaking for a certain period of time, the target antibody can be adsorbed to the surface of the magnetic adsorbent. Under the action of the external magnetic field, the target antibody can be quickly separated from the sample matrix with the magnetic beads. After washing to remove impurities, the analyte is finally eluted from the adsorbent by a suitable eluent, thereby achieving the purpose of separation and enrichment. Compared with other methods, magnetic bead-based antibody purification has great advantages, such as: (1) short purification equilibrium time, high purification efficiency, and simple operation; (2) rapid phase separation, not limited by sample heterogeneity and viscosity, and for samples with complex matrices, the problem of column clogging can be avoided by not using dispersed magnetic materials to fill the column; (3) easy to clean and elute, low consumption of organic solvents, and easy to automate. Therefore, magnetic bead-based antibody purification has great application potential.

[0003] Agarose antibody purification materials prepared by prior art have the advantages of high cost, low antibody loading, and difficult to control preparation methods. Specifically, the preparation of magnetic nanocomposites still faces the following urgent problems: (1) How to controllably prepare magnetic nanoparticles with strong magnetic response and good dispersibility and ensure their stability; (2) Effective connection and structural control of the interface between magnetic nanoparticles and functional coating materials are still challenges faced in the preparation of magnetic composites; (3) Considering the specific application of magnetic antibody purification materials, how to improve purification selectivity, recovery rate and repeatability still needs to be solved. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide nanomagnetic beads and a preparation method and application thereof. The nanomagnetic beads provided by the present invention have a large specific surface area and a high adsorption capacity, and can effectively improve the efficiency of antibody separation, purification and enrichment.

[0005] The present invention provides nano magnetic beads, which include Fe 3 O 4 The core of the nanomagnetic particle, the Fe 3 O 4 The surface of the nanomagnetic particles is coated with a silicon dioxide layer and a chitosan layer in sequence;

[0006] The nanomagnetic beads are coupled with affinity proteins, and the affinity proteins include at least one of protein A, protein G and protein L.

[0007] In some embodiments, the Fe 3 O 4 The particle size of the nanomagnetic particles is 100 to 800 nm;

[0008] The affinity protein is coupled to the nanomagnetic bead by modifying the functional groups on the surface of the chitosan, wherein the functional groups include maleimide and / or haloacetyl.

[0009] In some specific embodiments, the Fe 3 O 4 The particle size of the nanomagnetic particles is 100 to 300 nm. 3 O 4 The particle size of the nanomagnetic particles after being coated with a silicon dioxide layer and a chitosan layer in sequence is 150 to 350 nm;

[0010] The affinity protein is protein A, and the functional group is maleimide.

[0011] The present invention provides a method for preparing the nanomagnetic beads, comprising:

[0012] Step 1: Take Fe 3 O 4 Nano-magnetic particles, tetraethoxysilane and ammonia water are mixed and reacted to obtain Fe 3 O 4 @SiO 2 Magnetic beads;

[0013] Step 2: Take the Fe 3 O 4 @SiO 2 Magnetic beads, after neutralization precipitation method, in the Fe 3 O 4 @SiO 2 The surface of magnetic beads is coated with chitosan layer to obtain Fe 3 O 4 @SiO 2 @CS magnetic beads;

[0014] Step 3: Take the Fe 3 O 4 @SiO 2 @CS magnetic beads, after surface modification, are coupled with affinity proteins to obtain the nanomagnetic beads.

[0015] In some embodiments, in step 1,

[0016] The Fe3 O 4 The preparation method of nano magnetic particles comprises: taking ferric chloride hexahydrate and ethylene glycol and mixing them by ultrasonic, mixing them with anhydrous sodium acetate and sodium citrate by stirring, reacting under high pressure and high temperature, magnetically separating, and ultrasonically cleaning to obtain the Fe 3 O 4 Nanomagnetic particles.

[0017] In some embodiments, in step 1,

[0018] The mass ratio of the ferric chloride hexahydrate, the anhydrous sodium acetate and the sodium citrate is (1-3): (1-4) (0.1-0.5), and the high-pressure and high-temperature reaction comprises placing the stirred and mixed solution in a high-pressure reactor and reacting at 180-220° C. for 10-15 hours;

[0019] The Fe 3 O 4 After the nanomagnetic particles are ultrasonically dispersed in 80vol% to 90vol% ethanol solution, tetraethoxysilane and ammonia water are added, the final concentration of tetraethoxysilane is 1vol% to 3vol%, the final concentration of ammonia water is 0.1vol% to 0.3vol%, and the reaction time is 2 to 5h.

[0020] In some specific embodiments, in step 1,

[0021] The mass ratio of the ferric chloride hexahydrate, the anhydrous sodium acetate and the sodium citrate is 16.2:24:3, and the high-pressure and high-temperature reaction comprises placing the stirred and mixed solution in a high-pressure reactor and reacting at 200° C. for 12 hours;

[0022] The Fe 3 O 4 The nanomagnetic particles were dispersed in 300 mL of ethanol by ultrasonication, and 30 mL of deionized water, 5 mL of the tetraethoxysilane and 2 mL of 28% ammonia water were added. The reaction time was 3 h.

[0023] In some embodiments, in step 2, the neutralization precipitation method comprises:

[0024] S1, mixing chitosan, glacial acetic acid and ultrapure water in a conical flask, heating and stirring in a water bath to obtain a chitosan acetic acid solution;

[0025] S2, take the Fe 3 O 4 @SiO 2 After the magnetic beads and the chitosan acetic acid solution are ultrasonically mixed, the ultrasonically mixed solution is dispersed into a sodium hydroxide solution through a two-fluid nozzle, and the Fe 3 O4 @SiO 2 @CS magnetic beads.

[0026] In some embodiments, in S1, the mixed solution comprises: 10-30 mg / mL 95% deacetylated chitosan and 1 vol%-5 vol% glacial acetic acid, the relative molecular weight of the chitosan is 100-200 kDA, the water bath heating temperature is 50-65° C., and the stirring time is 1.5-3 h;

[0027] In S2, the solution after ultrasonic mixing includes 10 to 30 mg / mL of Fe 3 O 4 @SiO 2 The magnetic beads, the concentration of the sodium hydroxide solution is 30-50 g / L, the flow rate of the solution dispersed through the two-fluid nozzle after ultrasonic mixing is 0.3-0.8 mL / min, and the stirring reaction time is 1.5-3 h.

[0028] In some specific embodiments, in S1, the mixed solution includes: 20 mg / mL 95% deacetylated chitosan and 2 vol% glacial acetic acid, the relative molecular weight of the chitosan is 100-200 kDA, the water bath heating temperature is 60° C., and the stirring time is 2 h;

[0029] In S2, the solution after ultrasonic mixing includes 20 mg / mL of Fe 3 O 4 @SiO 2 The magnetic beads, the concentration of the sodium hydroxide solution is 40 g / L, the flow rate of the ultrasonically mixed solution dispersed through the two-fluid nozzle is 0.5 mL / min, and the stirring reaction time is 2 h.

[0030] In some embodiments, in step 3,

[0031] The surface modification comprises: taking the Fe 3 O 4 @SiO 2 CS magnetic beads, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide, maleimide butyric acid and acetonitrile were mixed, placed on a vertical mixer for reaction, magnetically separated and washed to obtain maleimide-modified Fe 3 O 4 @SiO 2 @CS;

[0032] The coupling with affinity protein comprises: taking the maleimide-modified Fe 3 O 4 @SiO2 @CS, affinity protein and phosphate buffer are mixed, placed on a vertical mixer for reaction, magnetically separated and washed to obtain the nanomagnetic beads.

[0033] In some embodiments,

[0034] In the surface modification, the acetonitrile solution obtained by mixing includes: 0.5-2 mg / mL of Fe 3 O 4 @SiO 2 @CS magnetic beads, 3-8 mg / mL 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 3-8 mg / mL N-hydroxysuccinimide, 3-8 mg / mL maleimidobutyric acid, and the reaction time is 1.5-3 h;

[0035] In the coupling with affinity protein, the maleimide-modified Fe 3 O 4 @SiO 2 The mass ratio of @CS to the affinity protein is (1-4):1, and the reaction time is 18-36 hours.

[0036] In some specific embodiments,

[0037] In the surface modification, the acetonitrile solution obtained by mixing includes: 1 mg / mL of the Fe 3 O 4 @SiO 2 @CS magnetic beads, 5 mg / mL 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 5 mg / mL N-hydroxysuccinimide and 5 mg / mL maleimidobutyric acid, the reaction time is 1.5 to 3 hours;

[0038] In the coupling with affinity protein, the maleimide-modified Fe 3 O 4 @SiO 2 The mass ratio of @CS to the affinity protein is 20:15, and the reaction time is 24h.

[0039] The present invention provides the use of the nanomagnetic beads or the nanomagnetic beads prepared by the preparation method in enriching and purifying antibodies.

[0040] The invention provides a kit for enriching and purifying antibodies, comprising the nanomagnetic beads or the nanomagnetic beads prepared by the preparation method.

[0041] Compared with the prior art, the present invention accurately and reasonably designs a nano magnetic bead with a core-shell structure, and provides a preparation method of the nano magnetic bead, which has controllability and flexibility, and is suitable for large-scale stable production and promotion and application. The magnetic material of the core-shell structure of the nano magnetic bead has a large specific surface area and high adsorption capacity. In the field of monoclonal antibody production, these magnetic materials can be used to pre-treat complex samples to achieve the purpose of effective separation, purification and enrichment, and reduce antibody purification costs. It has been verified by experiments that the magnetic nanoparticle IgG load prepared by the present invention can reach up to 173mg / mL. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Indicates Fe 3 O 4 Electron microscopic image of the particle size of nanomagnetic particles;

[0043] Figure 2 Indicates Fe 3 O 4 @SiO 2 Electron microscopic image of the particle size of nanomagnetic particles;

[0044] Figure 3 The chitosan magnetic composite obtained by the neutralization precipitation method is shown;

[0045] Figure 4 Chitosan-coated Fe 3 O 4 @SiO 2 Nanomagnetic particles;

[0046] Figure 5 The chitosan agarose magnetic beads obtained by the reverse phase emulsion method are shown;

[0047] Figure 6 The immunoglobulin bands obtained by separation and purification are shown, wherein M: protein marker, 1: IgG purified from a serum sample diluted 10 times, 2: IgG purified from a serum sample diluted 5 times, 3: IgG purified from a serum sample diluted 4 times, 4: IgG purified from a serum sample diluted 2 times. DETAILED DESCRIPTION

[0048] The present invention provides nanomagnetic beads and preparation methods and applications thereof. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described by preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0049] Antibody purification is a very important process in the production of monoclonal antibodies, accounting for more than 50% of downstream processing costs. Antibody purification materials usually work in the form of filling columns, which is relatively cumbersome to operate; magnetic materials can be directly dispersed in the analysis sample, operated by the action of the magnetic field, and have the characteristics of simplicity and easy automation. However, magnetic antibody purification materials must maintain the adsorption characteristics of general antibody purification materials while ensuring sufficient magnetic responsiveness and stability, so they are a more complex functional composite material; reasonable structural design and controllable synthesis are the basis and important guarantee for the preparation and application of antibody purification materials, and are also the problems to be solved by the present invention.

[0050] The specific implementation scheme of the present invention is as follows: In the solvothermal synthesis of magnetic nano-Fe 3 O 4 The particle surface is first coated with a dense layer of silicon dioxide, which not only effectively protects the stability of the magnetic core, but also lays the foundation for the subsequent coating of chitosan. The thickness and pore size of the chitosan layer can be controlled by adjusting the concentration of the chitosan precursor solution and the properties of the surfactant. The present invention uses acetic acid to dissolve chitosan and coats the silicon Fe 3 O 4 The particles are mixed and then added to an alkaline solution for neutralization and precipitation to prepare a chitosan magnetic complex. Afterwards, the surface amino groups of the chitosan are modified to maleimide. Finally, the thiol group at the tail end of the recombinant protein A is used to react with maleimide for Michael addition reaction at a specific pH to form a magnetic chitosan complex loaded with protein A. In addition to protein A, the proteins that have affinity with immunoglobulins include protein G, protein L, protein A / G, and protein A / G / L. Since the elution conditions required for protein A are milder, protein A is still the main antibody purification magnetic beads and fillers on the market.

[0051] In the preparation scheme designed by the present invention, different methods can be used to prepare magnetic nanoparticles, such as precipitation method and high temperature decomposition method, etc.; the chitosan layer in the core-shell structure can also be prepared by a method different from the present invention, and different surface functional groups can be used to fix protein A; even proteins (such as protein G, protein L, etc.) and specific polypeptides can be used to replace protein A. However, the basic ideas and purposes of these alternative methods are consistent with the present invention. It should be pointed out that for those skilled in the art, several improvements can be made without departing from the concept of the present invention, and these improvements should also be regarded as the scope of protection of the present invention.

[0052] The test materials used in the present invention are all common commercial products and can be purchased in the market.

[0053] Among them, Suzhou Nanovita Technology Co., Ltd.'s MagneStar MA-Protein A magnetic beads product, item number is MAFXPA-4000;

[0054] ProteinAMag Sepharose Xtra magnetic beads from Situofan, item number is 28967056.

[0055] The present invention will be further described below in conjunction with the embodiments.

[0056] Example 1: Fe 3 O 4 Preparation of nanomagnetic particles

[0057] 16.2 g of ferric chloride hexahydrate and 160 ml of ethylene glycol were first ultrasonically dissolved to form a transparent brown-yellow solution, and then 24 g of anhydrous sodium acetate and 3 g of sodium citrate were added and stirred to mix evenly. The mixture was placed in a high-pressure reactor and reacted in an oven at 200 degrees for 12 hours. The mixture was naturally cooled to room temperature and separated by a magnetic separator to obtain the product Fe 3 O 4 The nanoparticles were washed with anhydrous ethanol and ultrapure water for 3 times, each time using an ultrasonic cleaner. After washing, they were dispersed with anhydrous ethanol.

[0058] The prepared Fe 3 O 4 The particle size of nanomagnetic particles is 100-300 nanometers. Figure 1 .

[0059] Example 2: Fe 3 O 4 Silica coating of magnetic nanoparticles

[0060] Take the magnetic Fe prepared in the previous step 3 O 4 Nanospheres were dispersed in 300 ml of ethanol, 30 ml of deionized water was added, and ultrasonic dispersion was performed in an ultrasonic cleaner. The mixture was then transferred to a 500 ml round-bottom flask, 5 ml of tetraethoxysilane (TEOS) and 2 ml of 28% ammonia were added, and the reaction was stirred for 3 hours. The obtained product was washed twice with anhydrous ethanol and ultrapure water, and each time it was washed with an ultrasonic cleaner. Finally, it was dispersed with anhydrous ethanol.

[0061] The prepared Fe 3 O 4 @SiO 2 The particle size of nanomagnetic particles is 150-300 nanometers. Figure 2 .

[0062] Example 3: Fe 3 O4 @SiO 2 Chitosan coating of magnetic nanoparticles (neutralization precipitation method)

[0063] Weigh 2 g of 95% deacetylated chitosan with a 100-200 kDA, 2 ml of glacial acetic acid and 98 ml of ultrapure water in a conical flask, and heat and stir in a water bath at 60 degrees with a magnetic stirrer for 2 hours. 3 O 4 @SiO 2 , after magnetic separation to remove the ethanol preservation solution, wash it with ultrapure water for 3 times. Take 20 ml of the prepared chitosan acetic acid solution and add it, ultrasonically disperse it for 15 minutes, and then transfer it to a syringe. Weigh 40 g of sodium hydroxide and dissolve it in 1000 ml of ultrapure water, keep stirring. Use a two-fluid nozzle to inject chitosan / Fe 3 O 4 @SiO 2 The mixed liquid is dispersed into the sodium hydroxide solution, the gas phase is nitrogen with a pressure of 0.2MPa, and the liquid phase is chitosan / Fe 3 O 4 @SiO 2 The mixed solution was set at a flow rate of 0.5 mL / min by a syringe pump. The mixture was stirred rapidly for 2 hours. After stirring, the sodium hydroxide solution was recovered by magnetic separation, and the magnetic chitosan complex product was collected and washed three times with ultrapure water. Finally, the product was dispersed in ultrapure water. The morphology was observed by electron microscopy. Figure 3 shown.

[0064] Reference electron microscope Figure 4 , according to particle size analysis, chitosan-coated Fe 3 O 4 @SiO 2 The particle size of the nanomagnetic particles is 150-350 nanometers. Compared with Example 2, it can be seen that the thickness of the chitosan layer is in the range of about 50 nanometers.

[0065] Example 4: Fe 3 O 4 @SiO 2 Chitosan coating of nanomagnetic particles (inverse emulsion method)

[0066] Weigh 2 g of 95% deacetylated chitosan with 100-200 kDA, add 2 ml of glacial acetic acid and 98 ml of ultrapure water into a conical flask, and heat and stir at 60 degrees Celsius for 2 hours on a magnetic stirrer. Weigh 1 g of agarose and sodium chloride powder respectively, add 100 ml of ultrapure water into a conical flask, and heat and stir at 80 degrees Celsius for 2 hours on a magnetic stirrer. Then take 25 mg of the Fe 3 O 4 @SiO 2, after magnetic separation to remove the ethanol preservation solution, wash with ultrapure water three times. Take 2.0 ml of the prepared chitosan acetic acid solution and 0.5 ml of agarose solution and add them, ultrasonically disperse at 60 degrees Celsius for 30 minutes. Weigh 2.5 grams of Span-85 and dissolve it in 30 ml of isooctane, keep it at 80 degrees Celsius and stir at 250rpm for 30 minutes. Use a pipette to mix the chitosan / agarose / Fe 3 O 4 @SiO 2 The mixed solution is added dropwise to the above organic phase. Stir at 80 degrees Celsius and 500 rpm for 1 hour. Then add 300 microliters of 25% glutaraldehyde and continue stirring for 1 hour. Then add 500 microliters of 1M sodium hydroxide solution and continue stirring for 1 hour. After the reaction is completed, use a magnetic separator to separate the magnetic material. The organic phase can be recycled. After collecting the product chitosan agarose magnetic beads, wash them three times with ultrapure water. After that, place them in an 80 degree Celsius water bath for 3 hours to dissolve and remove the agarose. Finally, the product is dispersed in ultrapure water. The morphology is observed by electron microscopy as follows Figure 5 shown.

[0067] The results showed that compared with the product obtained by the reverse emulsion method, the product obtained by the neutralization precipitation method failed to form a complete sphere, but had more surface network structures and pores, and therefore had a larger specific surface area and potential protein binding sites.

[0068] Example 5: Modification of maleimide groups on the surface of magnetic chitosan complex and directional coupling of protein A

[0069] Directed coupling on the surface of chitosan magnetic complex requires modification of the amino groups on the surface of chitosan to maleimide. Take 4000 microliters of 10% (V / V) chitosan magnetic complex suspension, transfer to a 15 ml centrifuge tube, remove the supernatant by magnetic separation, and wash three times with acetonitrile. Weigh 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide and maleimide butyric acid, dissolve in 6 ml acetonitrile, including 1 mg / mL chitosan-coated Fe3O4@SiO2 nanomagnetic particles, 5 mg / mL 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 5 mg / mL N-hydroxysuccinimide, 5 mg / mL maleimide butyric acid. Add the prepared solution to the chitosan magnetic complex, mix well, and place on a vertical mixer for reaction for 2 hours. After the reaction is completed, remove the supernatant by magnetic separation, and then wash three times with acetonitrile. The product is maleimide-modified chitosan magnetic composite.

[0070] In addition to maleimide, iodoacetyl can also be used for directional coupling of protein ligands with only thiol groups at the tail end. In addition, epichlorohydrin, cyanogen bromide, N-hydroxysuccinimide, N, N-dicarbonylimidazole and other reagents can be used to activate the surface of natural polymers, thereby providing the functional groups required for coupling proteins. These functional groups mainly bind to the amino groups of proteins, thus affecting the surface domain of protein A.

[0071] Recombinant protein A with a cysteine ​​residue at the C-terminus can be coupled to the surface of chitosan activated by maleimide using the thiol group on the cysteine ​​residue to prepare a chitosan magnetic complex coupled with protein A. Recombinant protein A is the raw material with the largest cost proportion in the production process of antibody purification magnetic beads. Reducing the amount of recombinant protein A can significantly reduce the cost of producing protein A antibody purification magnetic beads. Taking 15 mg of recombinant protein A coupled to 1 ml of chitosan magnetic complex as an example, take 1 ml of maleimide-modified chitosan magnetic complex (which contains 20 mg of maleimide-modified Fe 3 O 4 @SiO 2 @CS) in a 15 ml centrifuge tube and washed once with ultrapure water. Dissolve 15 mg of recombinant protein A in 5 ml of pH 6.5 phosphate buffer (A280 reading was confirmed to be approximately 0.56 using NanoDrop).

[0072] The protein A solution was added to the chitosan magnetic complex, shaken and placed on a vertical mixer for reaction for 24 hours. After the reaction was completed, the supernatant was removed by magnetic separation and washed three times with a pH 6.5 phosphate buffer. The product was stored in a pH 6.5 phosphate buffer with 0.1% Proclin-300 added. The total volume was 5 ml. The amount of protein A bound to the protein A chitosan magnetic complex prepared in this scheme was greater than 5 mg / mL, and a high ability to bind to immunoglobulins (greater than 55 mg / mL) was obtained.

[0073] Example 6: Stepwise modification of maleimide groups on the surface of magnetic chitosan complex and directional coupling of protein A

[0074] In order to utilize more groups (mainly hydroxyl groups) on the surface of chitosan, before the maleimide modification of the surface of the chitosan magnetic composite, epichlorohydrin (ECH) can be used to modify the hydroxyl groups and part of the amino groups into epoxy groups, and then hexamethylenediamine can be used to convert the epoxy groups into amino groups. Take 4000 microliters of 10% (V / V) chitosan magnetic composite suspension, transfer it to a 15 ml centrifuge tube, remove the supernatant by magnetic separation, and wash it three times with pure water. Add 4.5 ml of dimethyl sulfoxide, 1.5 ml of pure water, and 60 mg of sodium hydroxide to the centrifuge tube and mix them evenly. After the centrifuge tube returns to room temperature, add 200 microliters of epichlorohydrin and place it on a vertical mixer for reaction for 2 hours. After the reaction is completed, the supernatant is removed by magnetic separation, and then washed three times with pure water. Dissolve 150 mg of hexamethylenediamine hydrochloride in 6 ml of 0.5 mol / L sodium hydroxide solution, then add the solution to the centrifuge tube, mix evenly, and place it on a vertical mixer for reaction for 16 hours. After the reaction is completed, the supernatant is removed by magnetic separation, and then washed three times with pure water and acetonitrile respectively. Weigh 100 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), N-hydroxysuccinimide and maleimide butyric acid, and dissolve them in 6 ml of acetonitrile. Add the prepared solution to the chitosan magnetic complex, mix well, and place it on a vertical mixer to react for 2 hours. After the reaction is completed, the supernatant is removed by magnetic separation, and then washed three times with acetonitrile. The product is a maleimide-modified chitosan magnetic complex. The subsequent coupling protein A scheme is the same as Example 5.

[0075] Example 7: Modifying aldehyde groups on the surface of magnetic chitosan complex and randomly coupling protein A

[0076] At present, the carrier materials with random coupling of protein A on the surface still occupy the mainstream in the market. Therefore, the protein A chitosan magnetic complex prepared by this scheme was also synthesized and the IgG purification ability was measured, and the IgG loading was compared with the directional coupling scheme. Random coupling requires the amino groups on the surface of chitosan to be modified to aldehyde groups. Take 4000 microliters of 10% (V / V) chitosan magnetic complex suspension, transfer it to a 15 ml centrifuge tube, remove the supernatant by magnetic separation, and wash it three times with acetonitrile. Measure 800 microliters of 50% glutaraldehyde, use pure water to make up to 10 ml, and obtain a 4% glutaraldehyde solution. Add the prepared solution to the chitosan magnetic complex, mix well, and place it on a vertical mixer to avoid light for 1 hour. After the reaction is completed, the supernatant is removed by magnetic separation, and then washed three times with pure water. The product is an aldehyde-modified chitosan magnetic complex.

[0077] The amino groups on the surface of the chitosan magnetic complex can be coupled with the amino groups of protein A to prepare a chitosan magnetic complex with random coupling of protein A. Taking 15 mg of recombinant protein A coupled to 1 ml of chitosan magnetic complex as an example, 1 ml of aldehyde-modified chitosan magnetic complex was taken in a 15 ml centrifuge tube and washed once with ultrapure water. 15 mg of recombinant protein A was dissolved in 5 ml of pH 7.8 phosphate buffer (A280 reading was confirmed to be about 0.56 using NanoDrop). The protein A solution was added to the chitosan magnetic complex, and after shaking, it was placed on a vertical mixer to react in the dark for 3 hours. After the reaction was completed, the supernatant was removed by magnetic separation and washed 3 times with pH 7.8 phosphate buffer. The product was stored in pH 7.8 phosphate buffer with 0.1% Proclin-300 added. The total volume was 5 ml. The amount of protein A bound to the protein A chitosan magnetic complex prepared in this scheme was greater than 5 mg / mL, and a higher ability to bind immunoglobulins (greater than 50 mg / mL) was obtained.

[0078] Example 8: Purification of immunoglobulins from human serum using magnetic chitosan complex coupled with protein A

[0079] Take the protein A magnetic chitosan complex prepared in Example 4 for experiment. Mix the above complex, take 100 μl into a 1.5 ml EP tube, and use a magnetic stand to adsorb the magnetic complex to the inner wall of the tube for 30-60 seconds. Use a pipette to remove the supernatant. Add pH 7.4 phosphate buffer to the EP tube, remove the EP tube and shake it thoroughly to wash. Put the EP tube back into the magnetic stand, adsorb for 30-60 seconds, and use a pipette to remove the supernatant. Repeat the washing 2-3 times.

[0080] Human serum diluted 10 times was used as the test sample. Take 1 ml and add it to the above-mentioned 1.5 ml EP tube. After thoroughly shaking and mixing, place it on a vertical mixer to react for 1 hour. After the reaction is completed, put the EP tube back on the magnetic stand, adsorb for 30-60 seconds, and use a pipette to remove the supernatant. Add pH 7.4 phosphate buffer to the EP tube, remove the EP tube and shake it thoroughly, and wash it. Put the EP tube back on the magnetic stand, adsorb for 30-60 seconds, and use a pipette to remove the supernatant. Repeat the washing 3 times to remove non-specifically adsorbed proteins and impurities. Elute the target antibody with 1 ml, 0.1M pH 2.0 glycine elution buffer, and then use a OneDrop spectrometer to determine the protein concentration in the eluate. Then perform SDS-PAGE detection with a gel concentration of 4-20%. As Figure 6 As shown, the protein A magnetic complex can separate high-purity immunoglobulins. The measured loading capacity of the chitosan magnetic complex can reach more than 55 mg / mL. Most commercially available agarose magnetic beads do not exceed 50 mg / mL.

[0081] Example 9: Purification of immunoglobulins in human serum at different dilution ratios using magnetic chitosan complex coupled with protein A

[0082] The amount of immunoglobulin bound to antibody purification magnetic beads will increase with the increase in the concentration of immunoglobulin in the sample solution until it reaches a plateau. Human serum samples with different dilution ratios were used as sample solutions with different immunoglobulin concentrations. The selected human serum IgG concentration was 14.25 mg / mL, which was diluted 10, 5, 4, and 2 times, respectively, to obtain test samples with IgG concentrations of 1.43, 2.85, 3.56, and 7.13 mg / mL. Antibody purification and elution were performed according to the steps of Example 8, and then the protein concentration in the eluate was determined using a OneDrop spectrometer. Then an SDS-PAGE test was performed with a gel concentration of 4-20%. Chitosan agarose magnetic beads and three chitosan magnetic materials coupled with protein A were tested using this scheme, and the results are shown in Tables 1 to 4 below.

[0083] Table 1. Binding capacity of chitosan magnetic complexes with directional coupling of protein A in samples with different IgG concentrations

[0084]

[0085] The results in Table 1 show that the maximum loading capacity of the chitosan magnetic complex of directional coupling protein A can reach 173 mg / mL.

[0086] Table 2. Comparison of binding capacity of chitosan agarose beads and chitosan magnetic complexes for directional coupling of protein A in samples with different IgG concentrations

[0087]

[0088] As shown in Table 2 above, the chitosan agarose magnetic beads prepared by the reverse emulsion method were used to purify the same concentration of IgG samples. The elution was performed using the same (pH 2) eluent. The IgG concentration obtained was significantly lower than that of the chitosan magnetic complex prepared by the neutralization precipitation method. The specific surface area of ​​the chitosan magnetic complex was significantly higher than that of the chitosan agarose magnetic beads when the specific surface area of ​​the two was measured by the BET method. At the same time, the surface morphology of the two was analyzed by SEM, and it was found that the surface of the chitosan magnetic complex had more porous structures ( Figure 3 and Figure 5 ), which can provide more protein binding sites.

[0089] Table 3. Binding capacity of chitosan magnetic complexes coupled to protein A after stepwise maleimide modification in samples with different IgG concentrations

[0090]

[0091] As shown in Table 3 above, the chitosan magnetic complex coupled with protein A after stepwise maleimide modification was used to purify four concentrations of IgG samples. The elution was performed using the same (pH 2) eluent, and the maximum IgG loading obtained was 140.1 mg / mL, which was slightly less than the product obtained by directional coupling with protein A. The reason is speculated to be that there is a side reaction of cross-linking with epichlorohydrin on the surface of chitosan, which enhances the physical strength of the chitosan complex while reducing the sites that can participate in the subsequent reaction.

[0092] Table 4. Binding capacity of chitosan magnetic complexes with random coupled protein A in samples with different IgG concentrations

[0093]

[0094] As can be seen from Table 4 above, the chitosan magnetic complex of random coupling protein A purified four concentrations of IgG samples, and eluted with the same (pH 2) eluent, and the maximum IgG load obtained could reach 60.5 mg / mL, which is significantly less than the product obtained by directional coupling protein A. Although the difference in the load of the two protein A chitosan magnetic complexes was less than 20 mg / mL when purifying low-concentration IgG samples, the chitosan load of directional coupling protein A increased more significantly when the sample IgG concentration increased. Therefore, the difference in the load between the two was obvious when purifying high-concentration IgG samples. Therefore, compared with the random coupling method, directional coupling protein A is beneficial to increase the IgG load of the material when consuming the same protein A.

[0095] At the same time, MagneStar MA-Protein A and Protein AMag Sepharose Xtra protein A agarose beads disclosed in the prior art were also tested using the above scheme, and the results are shown in Table 5 below.

[0096] Table 5. Binding capacity of MagneStar MA-Protein A and Protein AMag Sepharose Xtra protein A agarose beads in samples with different IgG concentrations

[0097]

[0098] The table above shows the IgG loadings obtained by purifying four concentrations of IgG samples with Nanovitamin and Situofan Protein A Magnetic Beads using the same (pH2) eluent for elution. The loading capacity of this model of Situofan is relatively low, while the loading capacity of Nanovitamin Protein A Magnetic Beads can reach up to 135.5 mg / mL. This loading capacity is less than the chitosan magnetic complex obtained by directional coupling of Protein A.

[0099] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Nanomagnetic beads, characterized in that, The invention comprises a core of Fe3O4 nano-magnetic particles, the surface of which is coated with a silicon dioxide layer and a chitosan layer in sequence; The nanomagnetic beads are coupled with affinity proteins, and the affinity proteins include at least one of protein A, protein G and protein L.

2. The nanomagnetic bead according to claim 1, characterized in that: The particle size of the Fe3O4 nanomagnetic particles is 100-800nm; Preferably, the particle size of the Fe3O4 nanomagnetic particles is 100 to 300 nm, and the particle size of the Fe3O4 nanomagnetic particles after the surface is coated with a silicon dioxide layer and a chitosan layer in sequence is 150 to 350 nm; The affinity protein is coupled to the nanomagnetic beads by modifying the functional groups on the surface of the chitosan, wherein the functional groups include maleimide and / or haloacetyl; Preferably, the affinity protein is protein A, and the functional group is maleimide.

3. The method for preparing the nanomagnetic beads according to claim 1 or 2, characterized in that: include: Step 1, Fe3O4 nanomagnetic particles, tetraethoxysilane and ammonia water are mixed and reacted to obtain Fe3O4@SiO2 magnetic beads; Step 2, taking the Fe3O4@SiO2 magnetic beads, coating the surface of the Fe3O4@SiO2 magnetic beads with a chitosan layer by a neutralization precipitation method to obtain Fe3O4@SiO2@CS magnetic beads; Step 3: Take the Fe3O4@SiO2@CS magnetic beads, modify their surfaces, and couple them with affinity proteins to obtain the nanomagnetic beads.

4. The preparation method according to claim 3, characterized in that: In the step 1, The preparation method of the Fe3O4 nano-magnetic particles comprises: taking ferric chloride hexahydrate and ethylene glycol and mixing them by ultrasonic method, mixing them with anhydrous sodium acetate and sodium citrate by stirring, reacting them under high pressure and high temperature, performing magnetic separation, and performing ultrasonic cleaning to obtain the Fe3O4 nano-magnetic particles; The mass ratio of the ferric chloride hexahydrate, the anhydrous sodium acetate and the sodium citrate is (1-3): (1-4) (0.1-0.5), and the high-pressure and high-temperature reaction comprises placing the stirred and mixed solution in a high-pressure reactor and reacting at 180-220° C. for 10-15 hours; After the Fe3O4 nanomagnetic particles are ultrasonically dispersed in an 80vol% to 90vol% ethanol solution, the tetraethoxysilane and ammonia water are added, the final concentration of the tetraethoxysilane is 1vol% to 3vol%, the final concentration of the ammonia water is 0.1vol% to 0.3vol%, and the reaction time is 2 to 5h.

5. The preparation method according to claim 3 or 4, characterized in that: In the step 2, the neutralization precipitation method comprises: S1, mixing chitosan, glacial acetic acid and ultrapure water in a conical flask, heating and stirring in a water bath to obtain a chitosan acetic acid solution; S2. After ultrasonically mixing the Fe3O4@SiO2 magnetic beads and the chitosan acetic acid solution, the ultrasonically mixed solution is dispersed into a sodium hydroxide solution through a two-fluid nozzle, and the Fe3O4@SiO2@CS magnetic beads are obtained after stirring, reaction, magnetic separation and washing.

6. The preparation method according to claim 5, characterized in that: In S1, the mixed solution includes: 10-30 mg / mL 95% deacetylated chitosan and 1 vol%-5 vol% glacial acetic acid, the relative molecular weight of the chitosan is 100-200 kDA, the water bath heating temperature is 50-65° C., and the stirring time is 1.5-3 h; In S2, the solution after ultrasonic mixing includes 10-30 mg / mL of the Fe3O4@SiO2 magnetic beads, the concentration of the sodium hydroxide solution is 30-50 g / L, the flow rate of the solution after ultrasonic mixing dispersed through the two-fluid nozzle is 0.3-0.8 mL / min, and the stirring reaction time is 1.5-3 h.

7. The preparation method according to any one of claims 3 to 6, characterized in that: In step 3, The surface modification comprises: taking the Fe3O4@SiO2@CS magnetic beads, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide, maleimide butyric acid and acetonitrile, mixing, placing on a vertical mixer for reaction, magnetically separating, and washing to obtain maleimide-modified Fe3O4@SiO2@CS; The coupling with affinity protein comprises: mixing the maleimide-modified Fe3O4@SiO2@CS, affinity protein and phosphate buffer, placing on a vertical mixer for reaction, magnetic separation, and washing to obtain the nanomagnetic beads.

8. The preparation method according to claim 7, characterized in that: In the surface modification, the mixed acetonitrile solution includes: 0.5-2 mg / mL of the Fe3O4@SiO2@CS magnetic beads, 3-8 mg / mL of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 3-8 mg / mL of N-hydroxysuccinimide, and 3-8 mg / mL of maleimidobutyric acid, and the reaction time is 1.5-3 h; In the coupling with the affinity protein, the mass ratio of the maleimide-modified Fe3O4@SiO2@CS to the affinity protein is (1-4):1, and the reaction time is 18-36 hours.

9. Use of the nanomagnetic beads according to claim 1 or 2 or the nanomagnetic beads prepared by the preparation method according to any one of claims 3 to 8 in enriching and purifying antibodies.

10. A kit for enriching and purifying antibodies, characterized in that: The invention comprises the nanomagnetic beads according to claim 1 or 2 or the nanomagnetic beads prepared by the preparation method according to any one of claims 3 to 8.